Biological function and epistemic normativity. (24th March 2017) - Sullivan-Bissett, Ema
Abstract : I give a biological account of epistemic normativity. My account explains the sense in which it is true that belief is subject to a standard of correctness, and reduces epistemic norms to there being doxastic strategies which guide how best to meet that standard. Additionally, I give an explanation of the mistakes we make in our epistemic discourse, understood as either taking epistemic properties and norms to be sui generis and irreducible, and/or as failing to recognise the reductive base of epistemic normativity. This explanation will appeal to the claim that the beliefs which constitute our epistemic discourse are false but adaptive, and are the outcome of a non-truth-tracking process. The opponents of my position are philosophers who take epistemic normativity not to be reducible in this way, and to involve sui generis properties and norms governing belief. The aim of the paper is to show that epistemic normativity can be explained by appeal to the biological functions of our mechanisms of belief-production.